PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO ANIMASI PADA MATERI SISTEM TATA SURYA DI KELAS VI SDN 1 CURUG - Rodiatul Ismayanah; Susilawati; Dewi Yulianawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of applying the Problem Based Learning model assisted by animated videos on the solar system material in class VI of SDN 1 Curug. The method used in this study is a quantitative approach with a pre-experimental research design, the type of design used is One Group Pretest Posttest design. This study took all 25 students of class VI of SDN 1 Curug. The learning outcomes of students with an average posttest score of 79.60 are much higher than the average pretest score of 53.60. Based on the results of the study, it can be concluded that there is a significant influence on student learning outcomes after using the Problem Based Learning model assisted by animated videos on the solar system material in class VI of SDN 1 Curug. The average posttest score of 79.60 is much higher than the average pretest score of 53.60, with the number of students who completed increasing drastically from 1 to 22. The results of the hypothesis test show a significance value of 0.000 < 0.05, which means the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, confirming a significant difference. In addition, the N-Gain test shows a value of 0.5501 which is included in the moderate category or 55.0133% effective interpretation, indicating that the use of this model is effective in improving learning outcomes.